Dasar dan Asas Pendidikan Islam Dalam Al-Qur’an dan Hadis - Basiah Basiah; Hotmarina Sari Harahap; Ramayanti Pulungan; Mardinal Tarigan; Marzuki Marzuki (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
The basis of Islamic education is the Koran and Hadith. These two foundations are the source of Islamic teachings that will guide the life of Muslims. In addition, there is a population principle, namely several educational sciences whose functions are needed to build an educational concept. Among the problems in life that will require our attention is education. Al-Quran has many statements about education, but they are still general in nature, so they will not be easy to use for human life. So in the verse that has been explained about education, we are obliged to study it carefully so that it can be demonstrated, understood and even applied to society so that it can lead to the right path. So basic education has to be something philosophical. Without an educational foundation, there is no education, because the actions of educators are baseless, aimless, without belief in the goodness and truth that they are doing. In addition, there are pedagogical principles, that is, some pedagogical sciences that are functionally necessary for the development of pedagogical concepts. Keywords: Al-Qur’an, Hadis, pedagogical concepts